Research Project MBPLE4Mobility: Mastering Complex Transportation Systems with a High Degree of Variability - Arestova, Anna; Homm, Daniel; Kallis, Lena; Kühn, Torsten; Portenlänger, Lukas; Rössler, Wolfgang; Schaffner, Johanna; Wagner, Heinrich; Wilder, Andreas; Zuccaro, Claudio (Tag des Systems Engineering (TdSE 2022), 2022)
The automation of rail traffic and the development of new components for automated electric vehicles require mastering a high level of complexity in terms of system architecture, development process, and especially product variability. Innovative approaches in the product development process will therefore become even more important in the future. Target of the publicly funded research project MBPLE4Mobility is to improve the approach of Model-Based Product Line Engineering (MBPLE) combining Model-Based Systems Engineering (MBSE) with Product Line Engineering (PLE). The developed approach is applied to areas in rail transport and automotive electric mobility with a high degree of product variability. As a result, costs, risks and throughput times of development processes should be reduced. This will be validated within the project. The present paper reports the current challenges for the partners involved in this project, how the challenges are intended to be addressed and presents exemplary solutions.<br